Pengaruh Tax Planning dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Property and Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Nursidin, M. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine and analyze whether Earning Per Share, Price Earning Ratio, Operating Costs, Operating Income have a significant effect on the Loan to Deposit Ratio in Private Banks listed on the Indonesia Stock Exchange for the 2019-2023 period. The research methodology used is the quantitative descriptive method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or figures. The data source is secondary data. Secondary data was obtained from www.idx.co.id to obtain the financial statements of Private Banks listed on the Indonesia Stock Exchange for the 2019-2023 period. The population in this study is the financial statements of Private Banks listed on the Indonesia Stock Exchange for the 2019-2023 period as many as 23 companies. The sample of this study amounted to 75 financial statements from 15 Private Banks Listed on the Indonesia Stock Exchange in 2019-2023. The data was analyzed using the multiple linear regression analysis method. The results of the analysis provide the equation Loan to Deposit Ratio = 0.984 + 0.000 Earning Per Share - 0.001 Price Earning Ratio - 0.116 Operating Costs Operating Income + e. The results of the study indicate that partially the variable has no influence but significant Earning Per Share on Loan to Deposit Ratio with tcount ttable values, namely -3.211 1.993 with a significant value 0.05, namely 0.002 0.05, then hypothesis 1 (first) in this study can be accepted.